2016
DOI: 10.5530/fra.2016.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Response in a Silkworm, Bombyx mori larvae to Dichlorvos insecticide

Abstract: Introduction: Antioxidant defense components protect insects by scavenging reactive oxygen species, leading to oxidative stress. We therefore investigated the effect of an organophosphate insecticide, dichlorvos, on superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT), glutathione S-transferase (GST) and glutathione reductase (GR) as antioxidative biomarkers in silk worm, Bombyx mori (L.), larvae. Methods: The newly hatched larvae were reared on mulberry leaves containing 0.01. 0.1, 1 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
6
1
2
Order By: Relevance
“…Furthermore, this gene was involved in protein processing in endoplasmic reticulum pathway (p value not significant; Table S3 (Supplementary file). Glutathione peroxidase (GPx) is involved in the antioxidant defense in silkworm and is considered as an antioxidative enzyme biomarker (Muthusamy and Rajakumar, 2016). The present study's results indicate that GPx was increased to overcome the toxic effects of silver.…”
Section: Go Categories Kegg Pathway Categories and Deg In Silkworm mentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, this gene was involved in protein processing in endoplasmic reticulum pathway (p value not significant; Table S3 (Supplementary file). Glutathione peroxidase (GPx) is involved in the antioxidant defense in silkworm and is considered as an antioxidative enzyme biomarker (Muthusamy and Rajakumar, 2016). The present study's results indicate that GPx was increased to overcome the toxic effects of silver.…”
Section: Go Categories Kegg Pathway Categories and Deg In Silkworm mentioning
confidence: 67%
“…The present study's results indicate that GPx was increased to overcome the toxic effects of silver. It has been reported that the glutathione peroxidase can play an important role in protecting cells from the reactive oxygen species induced by a pesticide (Muthusamy and Rajakumar, 2016). Previous studies demonstrated that neuropeptide F (NPF) in insects, a vertebrate neuropeptide Y (NPY) homolog, plays a key role in the feeding behavior, stress responses, and homeostasis regulation (Slade and Staveley, 2016;Nässel and Wegener, 2011).…”
Section: Go Categories Kegg Pathway Categories and Deg In Silkworm mentioning
confidence: 99%
“…Insects have evolved strong antioxidant defence mechanisms to overcome pesticides and xenobiotics. These antioxidant mechanisms primarily depend on enzymes such as glutathione transferase (GST), glutathione peroxidase (GPx), glutathione reductase (GR), catalase (CAT) and superoxide dismutase (Muthusamy & Rajakumar, ).…”
Section: Introductionmentioning
confidence: 99%
“…24 h a 9,6 µg L -1 de clorantraniliprol disminuyó significativamente la actividad enzimática de CAT. Se ha informado tanto la disminución (Adamski et al, 2003;Bϋyϋkgϋzel et al, 2013;Dere et al, 2015;Muthusamy & Rajakumar, 2016) como el aumento en la actividad CAT en diversas especies de insectos expuestas a diferentes grupos químicos de insecticidas (Adamski et al, 2003;Wu et al, 2011;Fahmy, 2012).…”
Section: Resultados Y Discusiónunclassified
“…También, se observó una disminución significativa de la actividad SOD en larvas de Galleria mellonella Linnaeus (Lepidoptera: Pyralidae) expuestas a 10 mg L -1 de malatión (Bϋyϋkgϋzel, 2009) y al insecticida botánico azadaractina (Dere et al, 2015). Asimismo, Muthusamy & Rajakumar (2016) reportaron una disminución significativa de SOD en gusanos de seda, Bombix mori Linnaeus (Lepidoptera: Bombycidae), expuestos a 5 mg L -1 del organofosforado diclorfós, y Bϋyϋkgϋzel (2006) detectó disminución en la actividad SOD en el himenóptero endoparásito Pimpla turionellae Linnaeus (Ichneumonidae), expuesto a malatión. Por el contrario, la exposición a los insecticidas ácido bórico, al neonicotinoide imidacloprid y al organofosforado clorpirifos produjo incrementos significativos en la actividad SOD en larvas de G. mellonella (Bϋyϋkgϋzel et al, 2013), en adultos de Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) (Gao et al 2013) y en larvas de Drosophila melanogaster Meigen (Diptera: Fig.…”
Section: Resultados Y Discusiónunclassified